Prayer - Baptist, Antony John; Cornille, C.; Mori, Geraldo Luiz de; Erp, Stephan van (Concilium, 2024)
"The focus of this particular issue will be the new contexts of prayer in the world and in the church, and on new forms of prayer that are being practiced today."--Page 8